Unveiling the neurotoxicity of inorganic and organic mercury in fish optic tectum: a morphometric and histopathological study - Carvalho, Teresa Patrícia Silveira (2021)
The optic tectum is a brain area that has been pointed out as particularly vulnerable in fish to inorganic mercury (iHg) and methylmercury (MeHg). The structural and functional integrity of this area is central for the maintenance of several behaviours including food search, predator escape and reproduction and is thus vital for fish survival. The current state of the art has knowledge gaps concerning the effects of iHg and MeHg on the optic tectum morphology, specifically in relation to these research questions: i) do iHg and MeHg differently affect specific layers of the optic tectum? ii) do iHg and MeHg target preferentially neurons or glial cells (or both indistinctly)? iii) is the optic tectum able to recover from iHg and MeHg exposure? iv) what is the most toxic form of Hg (iHg vs. MeHg) in the optic tectum? To answer these questions, two experiments exposing juvenile white seabream (Diplodus sargus) were performed under this dissertation, comprising both exposure (7 and 14 days; E7 and E14, respectively) and post-exposure (28 days; PE28) periods, namely: i) waterborne exposure to inorganic HgCl2 (2 μg L-1) and ii) dietary exposure to MeHg (8.7 μg g-1). Morphometric assessments were performed using stereological methods where the layers of the optic tectum were outlined, while its area as well as the number of neurons and glial cells were quantified. The histopathological analyses were performed per section and per layer of the optic tectum. ImageJ was used to outline and calculate the area analysed for posterior adjustment of results to the total area of each layer. Results showed that iHg exposure did not trigger the loss of neurons during the exposure periods (E7 and E14), while a decrease of glial cells was detected in a single layer of the optic tectum at E14. In the MeHg experiment, a decrease on the number of neurons and glial cells was found in several layers of the fish optic tectum during the exposure period. In the post-exposure timepoint (PE28), while both Hg forms triggered the loss of neurons, while only MeHg exposure led to a decrease on the number of glia cells. Histopathology pointed out a higher toxicity of MeHg in the optic tectum layers, particularly in the post-exposure period, while no significant alterations were found in fish previously exposed to iHg. Importantly, both forms of Hg target preferentially neurons rather than glial cells in the optic tectum. Additionally, it was difficult to perceive if Hg forms target specific layers of the optic tectum. Current findings point out iHg and MeHg as relevant neurotoxicants, with MeHg exposure leading to a higher neurotoxicity than iHg in the optic tectum of fish. After 28 days of post-exposure, neurotoxic effects of iHg and MeHg remained prominent, suggesting long-term effects of these Hg forms. Accordingly, the neurotoxic effects of iHg and MeHg in the fish optic tectum are hardly reversible over time, eventually compromising the fish well-being and survival. Moreover, the health condition of fish should be followed for several months after exposure to Hg forms.